A real-time hybrid method based on blade tip timing for diagnostics and prognostics of cracks in turbomachine rotor blades - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2020)
Dissertation (MEng)--University of Pretoria, 2019.